Hungarian Monitoring, 15 February 1988 . [Magyar rádiófigyelő], 1988. február 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Soviet-British foreign ministers' meeting - Inflation in Poland - Disappearance of Nazi files from West Berlin archive - Kurt Waldheim affair Domestic Affairs: - Kádár welcomes Soviet-Hungarian friendship association - Mátyás Szűrös begins talks in Roma - Supreme Court on last year's judgments, this year's work plan - Three Communist parties, including Hungarian Socialist Workers' Party (MSZMP), strive to create European atomic and chemical weapons zone - Environmental pollution in the Monori forests - Popular Front proposes a new national minorities law Economy: - Stock exchange conference to be held in Budapest - VAT can be claimed back - War of numbers in tax affairs Külpolitika: - Szovjet-brit külügyminiszteri találkozó - Infláció Lengyelországban - Náci iratok eltűnése a nyugat-berlini levéltárból - Kurt Waldheim ügy Belpolitika: - Kádár üdvözölte a szovjet - Magyar baráti társaságot - Szűrös Mátyás Rómában kezd tárgyalásokat - A Legfelsőbb Bíróság a tavalyi ítéletek tapasztalatai, idei munkaterv - Európai atom és vegyi fegyver övezet létrehozását szorgalmazza három kommunista párt, köztük az MSZMP - Környezetszennyezés a Monori - Erdőben - Új nemzetiségi törvény megalkotását javasolja a Népfront Gazdaság: - Tőzsdekonferencia lesz Budapesten - Visszaigényelhető az ÁFA - Számháború adóügyekben